2020
DOI: 10.3389/fped.2020.00081
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Relationship Between Respiratory Distress Syndrome and SP-A1 (rs1059057) Gene Polymorphism in Mongolian Very Premature Infants

Abstract: Aim: To study the relationship between rs1059057 polymorphism of pulmonary surfactant protein A1 (SP-A1) and respiratory distress syndrome (RDS) in Mongolian very premature infants.Methods: Applying the strategy of case-control study, 120 Mongolian RDS very premature infants (58 males and 62 females) in the western part of Inner Mongolia were selected as the case group, and 120 subjects of non-RDS very premature infants (56 males and 64 females) with the same nationality, same sex and similar gestational age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Regarding immature infant lungs, IHC of the right lung revealed a significant decrease in SP-A following acute impact injury, with gradual recovery observed between 24 and 72 h. Interestingly, we found that the SP-A changes in the left lung were similar to those seen in the injured lung. Moreover, in regions not directly impacted, bronchial SP-A changes mirrored those in lung tissue, showing a significant decrease immediately after injury and recovery within 24–72 h. Previous studies have revealed that post lung injury SP-A decreases ( 33 ), accompanying alveolar injury and secretion function, recruitment of neutrophils, and activation of macrophages that release a high number of inflammatory factors ( 34 ). This cascade exacerbates acute lung injury.…”
Section: Discussionmentioning
confidence: 86%
“…Regarding immature infant lungs, IHC of the right lung revealed a significant decrease in SP-A following acute impact injury, with gradual recovery observed between 24 and 72 h. Interestingly, we found that the SP-A changes in the left lung were similar to those seen in the injured lung. Moreover, in regions not directly impacted, bronchial SP-A changes mirrored those in lung tissue, showing a significant decrease immediately after injury and recovery within 24–72 h. Previous studies have revealed that post lung injury SP-A decreases ( 33 ), accompanying alveolar injury and secretion function, recruitment of neutrophils, and activation of macrophages that release a high number of inflammatory factors ( 34 ). This cascade exacerbates acute lung injury.…”
Section: Discussionmentioning
confidence: 86%
“…PCR-SSCP can be used to detect sequence differences, but its sensitivity decreases with increasing DNA fragment lengths. SSCP has been previously used in cancer prognosis ( 69 , 70 ), asthma ( 71 ), blood group test ( 72 ), Gilbert syndrome ( 73 ), diabetes ( 74 ), respiratory distress syndrome ( 75 ), male varicocele infertility ( 76 ), gastric mucosa ( 77 ), traditional Chinese medicine ( 78 ), bacterial DNA detection ( 79 ) and identification of Trichomonas vaginalis ( 80 ).…”
Section: Techniquesmentioning
confidence: 99%
“…Detection of somatic mutations in cancer, genes responsible for hereditary diseases, polymorphisms and other applications are described in detail at Kakavas et al [ 8 – 10 ]. Recent researches in the last 4 years shows dispersion of SSCP method in the above applications: on cancer prognosis [ 11 , 12 ], on asthma disease [ 13 ], on blood groups [ 14 ], on gilbert’s syndrome [ 15 ], on diabetes disease [ 16 ], on respiratory distress syndrome [ 17 ], on infertile men with varicocele [ 18 ], on gastric mucosa [ 19 ], on traditional Chinese medicine [ 20 ], detection of bacterial DNA [ 21 ], identification of trichomonas vaginalis [ 22 ].…”
Section: Medical Diagnosis Applicationsmentioning
confidence: 99%